1990
DOI: 10.1007/bf01734543
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of schizophrenic deficits by cognitive training: An evaluative study

Abstract: The significance of training programmes was assessed in reducing cognitive deficits in schizophrenics. In a controlled clinical trial, which included 15 experimental and 15 comparison subjects, training was shown to be effective with regard to more complex cognitive functions rather than on an elementary level. Results are discussed with regard to theoretical and practical implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
3

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(31 citation statements)
references
References 7 publications
2
26
0
3
Order By: Relevance
“…One study by Medalia et al (2000a) was excluded because the study group consisted of patients with different diagnoses. Twelve studies were selected for the review (Olbrich and Mussgay 1990;Hermanutz and Gestrich 1991;Benedict et al 1994;Burda et al 1994;Field et al 1997;Medalia et al 1998Medalia et al , 2000bMedalia et al , 2001Spaulding et al 1999;Wykes et al 1999;Bell et al 2001;Bellack et al 2001;van der Gaag et al 2002). These studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study by Medalia et al (2000a) was excluded because the study group consisted of patients with different diagnoses. Twelve studies were selected for the review (Olbrich and Mussgay 1990;Hermanutz and Gestrich 1991;Benedict et al 1994;Burda et al 1994;Field et al 1997;Medalia et al 1998Medalia et al , 2000bMedalia et al , 2001Spaulding et al 1999;Wykes et al 1999;Bell et al 2001;Bellack et al 2001;van der Gaag et al 2002). These studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…But do these effects generalize to other meaningful outcomes? Five studies have assessed the effects of training on level of symptomatology (Olbrich and Mussgay 1990;Hermanutz and Gestrich 1991;Medalia et al 1998;Spaulding et al 1999;Wykes et al 1999). Only the study by Medalia et al (1998) showed a significant decline in symptoms in favor of the training group.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, only 11 studies evaluated functional outcomes (16,19,20,22,24,25,27,29,(42)(43)(44), and this was the first meta-analysis to quantitatively demonstrate that cognitive remediation improved psychosocial functioning. Furthermore, the impact of cognitive remediation on functioning was moderated by several factors, including the provision of adjunctive psychiatric rehabilitation, cognitive training method, and patient age, suggesting potentially important factors for improving the impact of treatment programs.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the number of controlled studies of cognitive remediation, only six studies (16,19,21,(28)(29)(30) examined whether improvements in cognitive functioning were maintained at a posttreatment follow-up, precluding the exploration of moderators of treatment effects. The relative lack of data addressing this question may be important because different program, patient, or setting factors could influence the long-term maintenance of cognitive effects compared to short-term effects.Similarly, only 11 studies evaluated functional outcomes (16,19,20,22,24,25,27,29,(42)(43)(44), and this was the first meta-analysis to quantitatively demonstrate that cognitive remediation improved psychosocial functioning. Furthermore, the impact of cognitive remediation on functioning was moderated by several factors, including the provision of adjunctive psychiatric rehabilitation, cognitive training method, and patient age, suggesting potentially important factors for improving the impact of treatment programs.…”
mentioning
confidence: 99%
“…Die Trainingsfrequenz liegt bei etwa drei-bis viermal pro Woche für eine Zeitdauer von etwa einer Stunde pro Sitzung. Positive Veränderungen der kognitiven Defizite konnten in mehreren Therapiestudien gezeigt werden [19,20] Implikationen für die berufliche Integration Auch die Fähigkeit, dauerhaft einen Arbeitsplatz zu finden, ist für schizophrene Patienten deutlich beeinträchtigt. Schätzungswei-se 70 ± 85 % aller Betroffenen sind arbeitslos.…”
Section: Behaviourale Therapienunclassified